CONCEPTUAL ISSUES TRAINING FUTURE LAW ENFORCEMENT OFFICERS - Юрас, І. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In this article there were considered strategies of the specialists’ professional training in higher special educational institutions; it was given the characteristics of the non-stop educational new system; it was determined principles of the design-creative model’s creation of professional education